Physical multimorbidity and cancer prevalence in the National Health and Nutrition Examination Survey. (April 2021) - Tang, F.; Gates Kuliszewski, M.; Carrascal, A.; Vásquez, E.
Abstract: Objectives: As the US population ages, both cancer and multimorbidity become more common and pose challenges to the healthcare system. Limited studies have examined the association between multimorbidity and cancer prevalence in the US adult population. To help address this gap, we evaluated the associations between individual chronic conditions and all-site cancer, multimorbidity and all-site cancer, and multimorbidity and site-specific cancers. Study design: This is a cross-sectional study. Methods: Data from 10, 731 adults aged 20 years or older who participated in the 2013–2016 National Health and Nutrition Examination Survey were used in our study. Self-reported demographics, smoking status, sedentary behavior, body mass index, individual chronic conditions, multimorbidity status, cancer history, and cancer sites were assessed. Results: In our sample, the prevalence of having any type of cancer or multimorbidity was 9% (N = 861) and 38% (N = 4248), respectively. Respiratory conditions (multivariable-adjusted odds ratio [OR]: 1.3; 95% confidence interval [CI]: 1.1–1.6) and arthritis (multivariable-adjusted OR: 1.5; 95% CI: 1.2–1.8) were observed to be statistically significantly associated with having all-site cancer after adjusting for potential confounders. Having multimorbidity was also statistically significantly associated with having all-site cancer (multivariable-adjusted OR: 1.4; 95% CI: 1.2–1.7), cervical cancer (multivariable-adjusted OR: 2.6; 95% CI: 1.2–5.4), and bladder cancer (multivariable-adjusted OR: 2.8; 95% CI: 1.0–7.6). Conclusions: Multimorbidity was associated with all-site cancer, cervical cancer, and bladder cancer. The present study provides new evidence of the potential relationships between multimorbidity and cancer. Future longitudinal studies are warranted to clarify the temporality and potential biological mechanisms of the associations between multimorbidity and cancer. Article in a Tweet: Respiratory conditions and arthritis were observed to be significantly associated with having all-site cancer. Having multimorbidity is significantly associated with having all-site cancer, cervical cancer, and bladder cancer. The present study provides new evidence on the potential relationships between chronic conditions and all-site cancer and the relationships between multimorbidity and both all-site and site-specific cancers.